Development of low-cost capillary driven immunoassays for improved medical diagnostics - Link, Jeremy S., author; Henry, Charles S., advisor; Van Orden, Alan, committee member; Ackerson, Christopher J., committee member; Kipper, Matt J., committee member (Colorado State University. Libraries, 2023)
Rapid medical diagnostics are a crucial part of an effective healthcare system. While traditional laboratory diagnostic methods are well established and sensitive, they are also time consuming and expensive. Point of care (POC) diagnostics offer an attractive alternative to traditional testing for more affordable, fast results. Their simplicity allows for POC devices to be run quickly by untrained personnel, but the simplicity often limits their detection range and sensitivity. In this dissertation I discuss affordable, capillary-driven immunoassay devices that are capable of passively delivering reagents associated with a traditional well-plate enzyme linked immunosorbent assay (ELISA) to test strips. These devices are made of patterned and laser cut double-sided adhesive. When stacked and laminated together, the patterns cut from the layers form hollow microfluidic channels that can passively transport fluids through capillary action. The devices in this dissertation require only a single end-user step to perform a sandwich immunoassay, and signal from the enzyme/substrate reaction is detectable in under 30 min. Chapter 2 discusses the first application for visual detection of SARS-CoV-2 in these affordable capillary-driven immunoassay devices. The device in this chapter uses the enzyme horseradish peroxidase (HRP) and the substrate 3,3',5,5'-tetramethylbenzydine (TMB) to produce signal at the test line. Upon sample addition, the device channels fill, rehydrating the detection antibody and substrate dried on conjugate release pads that are stored in the channels of the device. Within 20 min, target, reagents, and washing steps are passively delivered to a nitrocellulose test strip containing a capture antibody test line. The device performance was compared to a well-plate ELISA, and the detection limits for inactivated SASR-CoV-2 were 86 PFU/mL and 8 PFU/mL for the device and ELISA respectively. A dose response curve was also generated for spiked nasal swab samples with a detection limit of 222 PFU/mL, demonstrating the device's use with complex biological samples. Chapter 3 expands on the work in Chapter 2 by demonstrating an alternative detection method. Chemiluminescent immunoassays are highly sensitive assays that rely on the energy provided by a chemical reaction to excite electrons. When the electrons move back to the ground state, they produce light that can be detected with an imager. In Chapter 3, I demonstrate the first example of a one-step, capillary driven immunoassay for chemiluminescent detection. The device is similar to that in Chapter 2, but the detection system relies on the reaction between HRP and a luminol based substrate to detect SARS-CoV-2 antigen. This work was done in collaboration with Burst Diagnostics Inc. and will be published when the appropriate patents and protections are in place. Chapter 4 introduces the first capillary driven enzyme-linked immunoassay for the simultaneous detection of multiple biomarkers. This multiplexed device is made of the same inexpensive materials as the previous chapters, but the microfluidic channels are designed in such a way that reagents are delivered to two, spatially separated test strips. This separation allows for simultaneous detection of two targets without cross-reactivity between reagents, reducing the chance of false positives. To demonstrate the purpose of this device, they were used to detect SARS-CoV-2 antigen on one test strip, and influenza antigen on the other. The illnesses caused by these two viruses lead to very similar symptoms, so distinguishing between the two illnesses from a single device would be beneficial. Dose response curves were gathered for both antigens, and the device was able to detect both diseases visually without false positives on the other test strip. Another form of multiplexed detection is simultaneous detection of two targets. To demonstrate this, SARS-CoV-2 and influenza antigen were detected simultaneously. Additionally, SARS-CoV-2 virus and c-reactive protein (CRP), a biomarker that can be used to determine the severity of COVID-19 cases, were detected simultaneously. This multiplexed assay has the potential to tell a healthcare provider 1) if an infection is or is not SARS-CoV-2, and 2) what level of care might be needed. This dissertation introduces three capillary driven immunoassay devices primarily for the use of detecting communicable diseases. The devices all run from a single end-user step, and fully automate the steps required for a more time consuming and expensive ELISA. Although the focus of this dissertation was on detecting communicable diseases, these devices can (and are) being further developed for chronic illnesses. In the future, by swapping the antibodies used in the immunoassay, the applications of these devices are innumerable. Additionally, different detection methods, such as fluorescent, electrochemical, and further chemiluminescent work could continue to push the detection limit down, widening the application of these devices even further.
Keywords: microfluidics; immunoassays; point of care diagnostics